Change in population structure, policy adjustment, and China’s public pension sustainability - Fan, Weiqiang; Meng, Jia; Yang, Hualei (PloS one, 2025)
This study assesses the impact of population structure changes and policy adjustment on public pension sustainability. The analysis is based on actuarial models for pension income, expenditure, and accumulated balance, assessed under varying scenarios. Based on the results, China’s pension financial situation will be in deficit by around 2028, with accumulated deficit potentially as high as RMB 147,411.037 billion in 2050 without population policy adjustment. Second, matching the fertility level with replacement level will only slightly ease the pension financial situation after 2041 and cannot change the deficit trend or the time of first appearance of deficit. The short-term situation may worsen slightly. Third, delaying the legal retirement age to 65 years significantly improves the pension financial situation and ensures no accumulated pension deficit before 2050. Lastly, although increasing economic growth and reducing pension growth can significantly improve the pension financial situation, if the accumulated pension deficit does not appear before 2050, the pension growth rate should be controlled below 0 and economic growth must double in future. In conclusion, to improve the financial status of pensions and ensure elderly welfare, we should focus on reducing pension growth, increasing economic growth, and postponing the statutory retirement age.